Recent Progresses in NIR-I/II Fluorescence Imaging for Surgical Navigation - Li, Songjiao; Cheng, Dan; He, Longwei; Yuan, Lin (Frontiers in Bioengineering and Biotechnology, 2021)
Cancer is still one of the main causes of morbidity and death rate around the world, although diagnostic and therapeutic technologies used to advance human diseases treatment. Currently, surgically resecting solid tumor is the most effective and prior remedial measure to treat cancer. Although medical treatment, technology and science advance significantly, it is challenging to completely treat this lethal disease. Near-infrared (NIR) fluorescence, including the first near-infrared region (NIR-I, 650-900 nm) and the second near-infrared region (NIR-Ⅱ, 1000-1700 nm), plays an important role in image-guided cancer surgeries due to its inherent advantages, such as great tissue penetration, minimal tissue absorption and emission light scattering, and low autofluorescence. By the virtue of high precision in identifying tumor tissue margins, there are growing number of NIR fluorescence-guided surgeries for various living animal models as well as patients in clinical therapy. Herein, this review introduces the basic construction and operation principles of fluorescence molecular imaging technology, and the representative application of NIR-Ⅰ/Ⅱ image-guided surgery in biomedical researches are summarized. Ultimately, we discuss present challenges and future perspectives in the field of fluorescence imaging for surgical navigation, and also put forward our opinions on how to improve the efficiency of the surgical treatment.